Effect of Enzyme-Assisted Pregelatinization on Edible Quality and Physicochemical Properties of Brown Rice - LIU Ming; ZAN Xue-mei; TAN Bin (Liang you shipin ke-ji, 2021)
In this study,pregelatinization and exogenous enzymes were combined to treat brown rice.The central combination test model was used to design a response surface analysis test with four factors and three levels,namely enzymolysis temperature,enzymolysis time,pregelatinization time and enzyme addition amount as independent variables,and the cooking time and sensory score as response values.At the same time,the effects of enzyme-assisted pregelatinization on the basic components and the thermodynamic properties of brown rice were studied.The results showed that there were significant influence on cooking time and sensory score of brown rice by enzymolysis temperature,enzymolysis time,pregelatinization time and enzyme addition amount.According to response surface analysis and validation tests,the optimal conditions were as follows:enzymolysis temperature was 61 ℃,enzyme addition amount was 2%,enzymolysis time was 127 min and pregelatinization time was 12 min.Under the optimal conditions,cooking time was 22.39 min and sensory score was 78.75.Enzyme-assisted pregelation technology significantly reduced lipids content of brown rice and was beneficial to the storage.Enzyme-assisted pregelation technology not only changed the gel temperature range of brown rice,but also made it easier to gelatinize.